Urban physical development and master planning in Zimbabwe: An assessment of conformance in the City of Mutare - Mabaso, Aaron; Shekede, Munyaradzi D.; Christa, Innocent; Zanamwe, Lazarus; Gwitira, Isaiah; Bandauko, Elmond (Journal for Studies in Humanities and Social Sciences, 2015)
Urban master plans play a critical role in the environmental management of urban landscapes in that they guide the physical developments that take place on and in them. In spite of this important role, there is limited knowledge on the degree to which their mapped objectives are achieved in actual terms. This gap in knowledge is mainly due to the lack of empirical methods for assessing plan implementation. In this study, we assess the degree of conformance of physical developments in the city of Mutare to master plan land use proposals. To do this, we carried out a GIS-based overlay analysis of the master plan and the land-use outcomes. We used an error matrix and Kappa Coefficient to assess whether land use proposals conform to existing developments in the city. The results of this study are that there is high overall conformance, although some proposed land uses do not conform to the master plan. We conclude that the adoption of GIS-based methods of compliance monitoring of land-use activities within urban environments provides an objective, rapid and efficient way of managing activities within such environments. We therefore recommend the adoption of such methods in urban areas for early detection of non-conformance and sustainable management of urban areas.